Prospective study of management and outcome of blunt abdominal trauma (solid organs and hollow viscus injuries) - Srivastava, Sandesh Kumar; Jaiswal, Anand Kumar; Kumar, Dinesh (International Surgery Journal, 2017)
Background: Blunt abdominal trauma is a leading cause of morbidity and mortality among all age groups. Many injuries may not manifest during the initial assessment and treatment period. Injury to intra-abdominal structures can be classified into 2 primary mechanism of injury-compression forces and deceleration forces. Compression or concussive force may result from direct blows or external compression against a fixed object. Deceleration forces causes stretching and linear shearing between relatively fixed and free objects. Methods: A prospective study of 48 patients admitted with blunt abdominal injuries in the department of surgery, B.R.D. Medical College Gorakhpur during a period of 1 year. Results: Majority of patients of blunt abdominal injuries in present study were in 11-20 year of age group followed by 31-40 year of age group followed by 41-50 year of age group. Female to male ratio was 7:1. In the present study 41% of patients were subjected to non-operative management. Conclusions: Males were pre-dominantly affected. Road traffic accident was the most common cause of injury. Though conservative management is successful in carefully selected patients, operative management remains the main stay of treatment.